Potensi Energi Mikrohidro di Daerah Irigasi (Studi Kasus di Wilayah Sungai Serayu Opak) - Bono Pranoto; Sinta Nur Aini; Hari Soekarno; Afida Zukhrufiyati; Harun Al Rasyid; Santi Lestari (Jurnal Irigasi, 2017)
Renewable energy development needs to be improved in order to overcome the problem of fossil energy sources that are increasingly depleted. Microhydro power plant is potential to be developed sinceIndonesia has a cluster of mountains where water spring can flow as sources of river water. In addition, microhydro is also potential from water flow in  irrigation networks. There are more than 48 thousands irrigation areas in Indonesia that potential to be utilized to increase the energy security of Indonesia. However, the problem is there is lack of information on the potency of microhydro energy that can be generated from irrigation areas. This study aims to identify and makea map of the potency of microhydro energy in Irrigation Areas of Serayu Opak River Basin, and to know the potency of microhydro energy that can be generated in  this region. The method used is to process image data through geospatial-based analysis and field verification.As a result, a map of the potency of microhydro energy has been produced and might be used as an indicative map showing irrigation channels which are potential for microhydrodevelopment. The amount of microhydro power in the irrigation area in SerayuOpak River Basinis about 26 MW.